(untitled) (CIPEEX, 2025)
This article investigates how religion can act as a means of building citizenship in contexts of social inequality, drawing on the perspectives of C.S. Lewis, Vishal Mangalwadi, Anthony Giddens, Philip W. Sutton, Artur R. I. L. Filho, Sheila B. Ost, and Wilian J. Bonete. The study aims to analyze how religious values and practices contribute to social inclusion, justice, and civic engagement. Methodologically, it combines bibliographic research with fieldwork through semi-structured interviews with representatives of six religious communities—Evangelical, Catholic, Islamic, Jewish, Buddhist, and Spiritist—thus ensuring diverse perspectives. The results show that religious communities promote citizenship through concrete actions such as food distribution, professional training, support for families, environmental projects, literacy programs, and social inclusion initiatives. These practices not only provide immediate assistance but also encourage civic participation, solidarity, and ethical responsibility. The theoretical framework reinforces that religious ethics, as highlighted by Lewis and Mangalwadi, strengthen values of justice, compassion, and human dignity, while the sociological contributions of Giddens and Sutton emphasize religion’s role in fostering social cohesion and transformative action. The findings confirm that religion, when authentically practiced, contributes significantly to mitigating inequalities and shaping citizens who are conscious, engaged, and committed to building a fairer and more inclusive society.